Community/ Public Participation Medico – Legal Concepts to Identify Unclaimed or Missing Dead Bodies from Public Mortuaries to Improve Public Health in Western Kenya - Maurice B. Silali; W. Odero; E. Rogena (Highlights on Medicine and Medical Science Vol. 1, 2021)
Community/Public participation in medico-legal form bench-mark of health determinants and quality integrated services towards criminal justice support in health. Globally, over 44 million cases of unclaimed bodies or missing dead persons (UCBOMDPs) occur annually, 88% of these cases are in Sub Saharan Africa. In western Kenya and Kenya the rate of UCBOMDPs from road traffic accidents accounts 30% and 10% respectively, 80% of these UCBOMDPs are associated with limited community participation / next of kins in identification of UCBOMDPs, thus prevailing chronic prevalence of occupational health and safety hazards in public mortuaries. The study aimed to assess extent of community participation, uptake of community mortuary services and awareness on quality medico-legal concepts, training, embalming and assess how of knowledge, attitude and practices (KAP) of service providers influence the uptake of medico-legal concepts to mitigate occupational health and safety hazards and improve health. In Exploratory and cross sectional, 235 respondents were investigated through purposive and saturated sampling using structured questionnaires, focus group discussions (FGDs), observations and key informant interviews (KII) guides to collect data. Analyzed statistical inferences and contents analysis to saturation, results showed, 94% of mortuary service providers in tier 4 were primary and secondary education drop outs of males, on contract jobs with limited access to quality forensic in mortuary science, contrarily to trained females and males counterparts from tiers 5 and 6 mortuary facilities on permanent. Embalming by gravitation method significant OD (1.2, 0.44). Prevalence of male being admitted as UCBOMDPs in the community was significant with, OD (8.3, 0.12), RR (0.33), 95% CI (1.23, 1.02), significance were associated with male deliberately leaving IDs in houses for anonymity. Community participation in medico-legal concepts were sufficient than Detective police with OD (0.43, 6.0), 95% CI (2.12, 1.34). Advocacy to empower community comprehensively and holistically in medico-legal concepts remains vital.